PARTICIPANTS OF THE «COLD CHAIN»: ANALYSIS OF COMPLIANCE WITH THE RULES OF THE GDP - I. A. Narkevich; V. A. Markova; D. A. Demidyonok (Разработка и регистрация лекарственных средств)
Manufacturer of domestic medical immunobiological preparations audited three transport companies on their degree of compliance with the rules of the GDP. Required measures were offered to eliminate detected violations.